Exploring Protest Theatre through the Lens of Ola Rotimi’s Hopes of the Living Dead - Josiah Adewale APALOWO; Maharanny Setiawan Poetri (Britain International for Academic Research (BIAR-Publisher), 2024)
Theatre not only entertains but also educates and motivates the society, which qualifies it as a weapon against societal vices and socio-political unrest in several countries to avoid dystopian societies. This paper focuses on the view of revolution, and how Rotimi uses his play to reflect revolutionary aesthetics and tendencies. This paper adopts Marxist ideology of Georg Lukacs’ Reflection Model in expounding social realities of class consciousness and struggles. The model was utilised in processing the specimen play to reflect the motivating ideology of quest for freedom and agitation for survival in a society bedeviled by oppression and social inequality. Resting on the pedestal of qualitative research methodology, narrative Research model is used in probing into the primary text. This paper discovered that the primary text was used by the playwright as a means to sensitise the society to have a good knowledge of their rights to demand a classless and egalitarian society. It also revealed that those who are interested in true revolution must never resign to fate. This paper concludes that Rotimi used his play to purge the ills of the society and recommends that committed African writers should commit their works to the emancipation of the oppressed and see revolution as an instrument of change and not violence.